Cultures of piety : medieval English devotional literature in translation - Bartlett, Anne Clark, 1960-; Bestul, Thomas H. (Thomas Howard), 1942- (Cornell University Press, 1999)
Devotional texts in late medieval England were notable for their flamboyant piety and their preoccupation with the tortured body of Christ and the grief of the Virgin Mary. Generations of readers internalized and shaped the "cultures of piety" represented by these works. Anne Clark Bartlett and Thomas H. Bestul here gather seven examples of this literature, all written in the period 1350-1450, one in Anglo-Norman, the remainder in Middle English. (The volume includes an appendix containing the original texts of the latter six pieces.) The collection illustrates the polyglottal, conflicting, and often polemical nature of devotional culture in the Middle Ages. It provides a valuable context for and interesting counterpoint to the Canterbury Tales and other classic works of late medieval England. The introduction and the translators' headnotes discuss crucial aspects of the texts' histories and thematics, including the importance of the body in spiritual practices, the development of female patronage and of a wide audience for this literature, and the indivisibility of the political and the religious in medieval times